Impact of country of birth on hospital admission for women of childbearing age in Sweden: a five year follow up study. Issue 11 (4th November 2003) - Robertson, E; Malmström, M; Sundquist, J; Johansson, S-E
Abstract : Study objective: This study examines whether morbidity, defined as the first psychiatric hospital admission and the first somatic hospital admission, differs among subgroups of foreign born and second generation (that is, native born with at least one parent born abroad) women compared with Swedish born women (that is, with both parents native born) after adjusting for sociodemographic factors. Design Setting: In this follow up study the population consisted of 1 452 944 women, of whom 369 771 have an immigrant background (including second generation immigrants), aged 20–45 years. The population of 31 December 1993 was followed up to 31 December 1998. Differences in risk (hazard ratio) between different groups of immigrant women were estimated, adjusting for age, marital status, number of children, and disposable income. Main results: All four groups of foreign born women had higher age adjusted risks (HRs varied from 1.44 to 1.67) for a first psychiatric hospital admission than Swedish born women. The risk decreased only marginally when the sociodemographic factors were taken into consideration. Additionally, second generation women also had a higher age adjusted risk (HR = 1.42; CI = 1.37 to 1.48) than Swedish born women. The risk decreased only slightly in the main effect model. However, on analysing country of birth and first somatic hospital admissions, only non-European refugee women showed an increased age adjusted risk (HR = 1.26; CI = 1.24 to 1.29), which remained after adjusting for sociodemographic factors. Conclusions: Foreign born and second generation women of childbearing age had a higher risk than Swedish born women for a first psychiatric hospital admission. However, only non-European refugees were at higher risk of somatic hospital admissions.